MIRERC082/2025: Effect of Innovative Instructional Strategies on Literacy Skills Acquisition among Lower Grade Learners in Public Primary Schools of Meru County, Kenya.” - Nyaga, Florence Wawira; Njagi , Kageni; Thuranira , Mercy (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Effective literacy instruction in early childhood education requires the application of instructional strategies that are developmentally appropriate and pedagogically sound. Teachers’ competence in selecting and implementing suitable methods plays a critical role in enhancing learners' acquisition and retention of literacy skills. This study will seek to evaluate the effectiveness of selected instructional strategies: phonics based instructional strategies, graphic organizers, interactive read alouds and visual support strategies on literacy skills acquisition among lower grade learners in public primary schools in Meru County, Kenya. The study will be guided by four specific objectives: to evaluate the effect of phonics based instructional strategies, assess the effect of graphic organizers, investigate the impact of interactive read aloud strategies, and determine the influence of visual support strategies on literacy skills acquisition. Grounded in the Constructivist Theory of Learning and Vygotsky’s Sociocultural Theory, the study will adopt a descriptive survey research design and will be conducted in selected public primary schools in Meru County. The target population will comprise of 11038 individuals including 9413 Grade 3 learners, 837 Grade 3 class teachers, 747 head teachers, and 41 Curriculum Support Officers (CSOs). A multistage sampling approach, involving stratified, simple random and purposive techniques, will be used to select a sample of 329 learners, 30 class teachers, 22 head teachers, and 5 CSOs. Data will be collected through questionnaires for learners and teachers, observation checklist for teachers and interview schedules for head teachers and CSOs. Validity of the instruments will be ensured through expert judgment and pilot testing, while reliability will be estimated using Cronbach’s Alpha, with a coefficient of 0.70 or above considered acceptable. Quantitative data will be analyzed using descriptive statistics (frequencies and percentages) and inferential statistics, specifically logistic regression at the 0.05 significance level. The findings will have implications for curriculum implementation, literacy policy development, and the enhancement of early grade reading outcomes in Kenya and comparable educational settings